The effect of post-processing operations on surface characteristics of 316L stainless steel produced by selective laser melting - KAYNAK, YUSUF (ELSEVIER, 2019)
Metal additive manufacturing is an emerging method to fabricate components used in the aerospace and biomedical industries. However, one of the significant challenges in this approach is the surface quality of the fabricated components. After metal additive manufacturing operations, post-processing is essential to meet the expected surface quality. This study presents the surface characteristics of as-built specimens manufactured by selective laser melting (SLM), where improvement of the surface can be achieved by post-processing operations. The post-processing operations in focus are finish machining (FM), vibratory surface finishing (VSF) and drag finishing (DF) operations. Surface topography, average surface roughness, microhardness, microstructure and XRD analysis have been carried out to examine the surface characteristics resulting from the post-processing operations. This study demonstrates that the drag finishing operation can be used for post-processing to meet the surface quality requirement of SLM manufactured parts.
Keywords: Additive manufacturing; Selective laser melting; 316L stainless steel; Post-processing; ROUGHNESS; BEHAVIOR